An easy synthesis of nitrogen and phosphorus co-doped carbon dots as a probe for chloramphenicol. Issue 54 (4th September 2020) - Zuo, Pengli; Chen, Zhongguang; Yu, Fengling; Zhang, Jinyu; Zuo, Wei; Gao, Yanli; Liu, Qingyou
Abstract : The spontaneous synthesis of nitrogen and phosphorus co-doped carbon dots was reported, and they were used as a probe for chloramphenicol. Abstract : Heteroatom doping in carbon dots (CDs) was found to be an efficient way to regulate the structure of electronic energy levels and enhance the fluorescence characteristics of CDs. Nevertheless, most reported fabrication processes of heteroatom-doped CDs are rigorous and complex. Herein, a facile and novel strategy was developed to rapidly prepare nitrogen and phosphorus co-doped CDs (N, P-CDs) using acetic acid as the carbon source, and arginine, 1, 2-ethylenediamine (EDA) and diphosphorus pentoxide as the dopants, respectively. The optical, morphological and structural characterizations of the synthesized N, P-CDs were investigated via UV and photoluminescence spectroscopy, X-ray photoelectron spectroscopy, TEM, and FT-IR spectroscopy. The N, P-CDs display outstanding fluorescence stability under high ionic strength (1.6 M KCl), and long time UV irradiation, indicating that they can be used as favorable candidates for fluorescent probes. The fluorescence of N, P-CDs was selectively quenched by chloramphenicol (CAP) with a short response time. The linear range of the response to CAP was from 0.8 to 70 μM with a limit of detection of 0.36 μM (S/N = 3). Notably, the fabricated N, P-CDs were employed for the highly selective and sensitive detection of CAP in milk samples, indicating their potential applications in biologically related areas.